1982
DOI: 10.1037/0012-1649.18.6.922
|View full text |Cite
|
Sign up to set email alerts
|

Further studies of the Tower of Hanoi problem-solving performance of retarded young adults and nonretarded children.

Abstract: Retarded adolescents and young adults, with a mean mental age of 10.23 years, and nonretarded children, with a chronological age ranging from 5.42 to 10.50 years, were given four-to seven-step Tower of Hanoi problems that differed in type of goal state. Overall performance levels of the kindergarten, first-grade, and retarded groups were the same but were reliably below the performance level of third and fourth graders. Performance differences were related to the minimum number of steps needed for a problem's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
2

Year Published

1992
1992
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 7 publications
(14 reference statements)
1
38
0
2
Order By: Relevance
“…Some investigations of young adults with ID have reported performance levels below mental age (MA), for example on the problem solving task Tower of Hanoi (e.g. Borys, Spitz & Dorans, 1982;Byrnes & Spitz, 1977;Spitz, Webster & Borys, 1982;Vakil, Shelef-Reshef & Levi-Shiff, 1997). Other studies have reported mental age appropriate performance on Tower tasks (Numminen, Lehto, Ruoppila, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Some investigations of young adults with ID have reported performance levels below mental age (MA), for example on the problem solving task Tower of Hanoi (e.g. Borys, Spitz & Dorans, 1982;Byrnes & Spitz, 1977;Spitz, Webster & Borys, 1982;Vakil, Shelef-Reshef & Levi-Shiff, 1997). Other studies have reported mental age appropriate performance on Tower tasks (Numminen, Lehto, Ruoppila, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Nine-year-old children were chosen for this study because 9 is the age when children can, on their own, solve the Tower of Hanoi puzzle at least some of the time (Byrnes & Spitz, 1979). Although 4-and 5-year-old children are able to solve the problem, they do so only when exceptionally intelligent (Kanevsky, 1989), when given experimenter support (Kanevsky, 1989;Klahr & Robinson, 1981), or when given an abbreviated task (Borys, Spitz, & Dorans, 1982;Klahr & Robinson, 1981;Spitz, Webster, & Borys, 1982). 2.…”
Section: Notesmentioning
confidence: 99%
“…This mechanism also explains why illegal moves are attempted in states where backward moves or pauses are observed. In their analysis of Tower of Hanoi problem-solving protocols, Spitz, Webster, and Borys (1982) reported that "Only in the retarded group did the rule violations increase (from 18% to 33%) from the four-step to the seven-step problem.... These data suggest that the retarded subjects understood the rules but occasionally restored to violations when they could find no ready solution to the problem" (p. 926).…”
Section: The Constraint Elimination Modelmentioning
confidence: 98%